Depressive symptoms in family caregivers of elderly people with Alzheimer's or other dementia (Research, Society and Development, 2021)
The objective was to analyze the perception of the presence of depressive symptoms in family caregivers of elderly people with Alzheimer's disease or other dementias. Exploratory-descriptive, quantitative study. A semi-structured questionnaire and three psychometric scales were used to assess depressive symptoms. Sample consisting of 51 family caregivers. Statistical analysis using Fisher's exact test and test for comparison of proportions. 50 caregivers presented depressive symptoms with predominant mild to moderate intensity, 27 (52.9%) felt depressed, 23 (45.1%) did not feel sick, although they identified possible factors for psychological distress and related care the demented elderly person as the main factor for their illness; 96% reported caring for the elderly as a cause of illness. Most caregivers pointed to lack of family support, symptoms and progression of the disease as the main factors for depression, they did not receive any type of intervention for their psychological suffering. Early diagnosis and interventions to prevent the suffering of family caregivers are needed.